Dialectic of enlightenment - Adorno, Theodor W. 1903-1969; Horkheimer, Max; Cumming, John (New York Continuum, 1997)
Dialectic of Enlightenment is undoubtedly the most influential publication of the Frankfurt School of Critical Theory. Written during the Second World War and circulated privately, it appeared in a printed edition in Amsterdam in 1947. "What we had set out to do," the authors write in the Preface, "was nothing less than to explain why humanity, instead of entering a truly human state, is sinking into a new kind of barbarism